Land Tenure Insecurity, Fragmentation and Crop Choice: Evidence from Uganda - Mwesigye, Francis; Barungi, Mildred (The African Economic Research Consortium, 2021)
This study uses household, parcel, and plot-level data to analyze the effect of land tenure insecurity and land fragmentation on crop choice. We use formal land titling as a proxy for de jure land rights, and the perceived transfer rights over parcels as a proxy for de facto land rights. Using two-part model, the study shows that both de jure and de facto land rights significantly increase the likelihood of planting perennial commercial crops, and increase the hectares allocated to commercial crops. The results also show that when the rights to land are weak (i.e., no land titling and no transfer rights), farmers tend to grow annual crops.